Science of Interstellar - Thorne, Kip S.; Nolan, Christopher, 1970- (New York : W.W. Norton & Company, 2014)
"Interstellar, from acclaimed filmmaker Christopher Nolan, takes us on a fantastic voyage far beyond our solar system. Yet in The Science of Interstellar, Kip Thorne, the physicist who assisted Nolan on the scientific aspects of Interstellar, shows us that the movie's jaw-dropping events and stunning, never-before-attempted visuals are grounded in real science. Thorne shares his experiences working as the science adviser on the film and then moves on to the science itself. In chapters on wormholes, black holes, interstellar travel, and much more, Thorne's scientific insights many of them triggered during the actual scripting and shooting of Interstellar, describe the physical laws that govern our universe and the truly astounding phenomena that those laws make possible."--
A scientist in Hollywood : the genesis of Interstellar -- Foundations. Our universe in brief ; The laws that control the universe ; Warped time and space, and tidal gravity ; Black holes -- Gargantua. Gargantua's anatomy ; Gravitational slingshots ; Imaging Gargantua ; Disks and jets ; Accident is the first building block of evolution -- Disaster on earth. Blight ; Gasping for oxygen ; Interstellar travel -- The wormhole. Wormholes ; Visualizing Interstellar's wormhole ; Discovering the wormhole : gravitational waves -- Exploring Gargantua's environs. Miller's planet ; Gargantua's vibrations ; Mann's planet ; The Endurance -- Extreme physics. The fourth and fifth dimensions ; Bulk beings ; Confining gravity ; Gravitational anomalies ; The professor's equation ; Singularities and quantum gravity -- Climax. The volcano's rim ; Into Gargantua ; The tesseract ; Messaging the past ; Lifting colonies off Earth -- Where can you learn more?
"Foreword by Christopher Nolan"--Cover.
Includes bibliographical references (pages 305-309) and indexes.
Keywords: Interstellar (Motion picture); Science in motion pictures